Mechanisms of ammonia activation and ammonium ion inhibition of quinoprotein methanol dehydrogenase: A computational approach - Reddy, Swarnalatha Y. (National Academy of Sciences, 2004)
The mechanism of methanol oxidation by quinoprotein methanol dehydrogenase (MDH·PQQ) in combination with methanol (MDH·PQQ·methanol) involves Glu-171 [Image: see text] [Formula: see text] general base removal of the hydroxyl proton of methanol in concert with hydride equivalent transfer to the [Image: see text] quinone carbon of pyrroloquinoline quinone (PQQ) and rearrangement to hydroquinone (PQQH(2)) with release of formaldehyde. Molecular dynamics (MD) studies of the structures of MDH·PQQ·methanol in the presence of activator NH(3) and inhibitor [Formula: see text] have been carried out. In the MD structure of MDH·PQQ·methanol·NH(3), the hydrated NH(3) resides at a distance of ≈24 Å away from methanol and the ortho-quinone portion of PQQ. As such, influence of NH(3) on the oxidation reaction is not probable. We find that [Formula: see text] competes with the substrate by hydrogen-bonding to Glu-171 [Image: see text] [Formula: see text] such that the [Formula: see text] complex is not reactive. Ammonia readily forms imines with quinone. Imines are present in solution as neutral ([Image: see text]) and protonated ([Image: see text]) species. MD simulations establish that the [Image: see text] derivative of [Formula: see text] structure is unreactive because of the nonproductive means of methanol binding. The structure obtained by the MD simulations with the neutral [Image: see text] imine of MDH·PQQ(NH)·methanol structure is similar to the reactive MDH·PQQ·methanol complex. This active site geometry allows for catalysis of hydride equivalent transfer to the [Image: see text] of PQQ(NH) by concerted Glu-171 [Image: see text] [Formula: see text] general-base removal of the H [Image: see text] OCH(3) proton and Arg-324 [Image: see text] H(+) general-acid proton transfer to the imine nitrogen. Enzyme-bound [Image: see text] derivative of PQQ [PQQ(NH)] and CH(2)O product are formed.